Numerical Solution of Second‐Order Impulsive Differential Equations With Loadings Subject to Integral Boundary Conditions - Kadirbayeva, Zhazira; Kadirbayeva, Roza (Mathematical methods in the applied sciences, 2025)
ABSTRACT In this paper, we present a computational method for solving the second‐order impulsive differential equations with loadings subject to integral boundary conditions based on the Dzhumabaev parametrization method. The idea of this method involves introducing additional parameters, reducing the original problem to solving a system of linear algebraic equations. The system's coefficients and right‐hand side are determined by solving Cauchy problems for ODEs and by calculating definite integrals. Four examples are provided to show the effectiveness and feasibility of the main results.